Meredupnya Media Cetak, Dampak Kemajuan Teknologi Informasi - Budi Arista Romadhoni (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2018)
The closing of national and international print media is the impact of technological development today. Print media is faced with the high cost of production and the change of society using mass media to seek information. Invention Information technology and communication that allows all forms of information to digital create a major impact on the media, especially print media. Online media provides a new color for the press and news readers, the news is fast, easy to access, and cheap. Media that can not keep up with technology will be closed.